DESIGNING ARDUINO-BASED INTEGRATED MOTORCYCLE PARKING SYSTEM AT PARKING AREA OF IBI DARMAJAYA - Tri Suratno; Nurfiana - (Proceeding International Conference on Information Technology and Business, 2018)
The parking area for IBI Darmajaya employees is the parking area where IBI Darmajaya employees put their vehicles. The problem statement of this research was the high number of IBI Darmajaya students putting their vehicle in the parking area for IBI Darmajaya employees due to limited parking space. This problem was able to be overcome by designing a system to open an access into the parking area through fingerprint system as the identifier (input) and Arduino Uno as the main controller. This system consisted of 4 main components i.e., the fingerprint sensor, the ultrasonic sensor, the servo motor, and the parking bar. The parking bar control system used Arduino Uno-based fingerprint system that was useful to shorten the verification process so that the vehicle was able to get into the parking area. The result of this research was that the fingerprint system-based parking bar control was able to save the 1,000 employee fingerprint records. An average for matching fingerprints to the closing bars was 4.86 seconds form the entrance bar and 4.8 seconds to the exit bar with 450 cm of the maximum distance between the ultrasonic sensor and the vehicle. Keywords: Parking; Microcontroller; Arduino; Fingerprint